2014
DOI: 10.3189/2014jog13j148
|View full text |Cite
|
Sign up to set email alerts
|

A distributed energy-balance melt model of an alpine debris-covered glacier

Abstract: ABSTRACT. Distributed energy-balance melt models have rarely been applied to glaciers with extensive supraglacial debris cover. This paper describes the development of a distributed melt model and its application to the debris-covered Miage glacier, western Italian Alps, over two summer seasons. Subdebris melt rates are calculated using an existing debris energy-balance model (DEB-Model), and melt rates for clean ice, snow and partially debris-covered ice are calculated using standard energy-balance equations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
89
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 48 publications
4
89
0
Order By: Relevance
“…8 in the terminus zone. However, other areas of the ablation zone are affected by a thin and patchy layer of debris or aerosol, which is likely to increase ablation through local albedo reduction (Fyffe et al, 2014). Although quantification of the effects of debris on melt is beyond the scope of this study, it would be expected that impacts of thick morainic debris and thin patchy debris elsewhere will tend to compensate in overall melt estimations for the glacier.…”
Section: Modelling Approach and Uncertaintiesmentioning
confidence: 99%
“…8 in the terminus zone. However, other areas of the ablation zone are affected by a thin and patchy layer of debris or aerosol, which is likely to increase ablation through local albedo reduction (Fyffe et al, 2014). Although quantification of the effects of debris on melt is beyond the scope of this study, it would be expected that impacts of thick morainic debris and thin patchy debris elsewhere will tend to compensate in overall melt estimations for the glacier.…”
Section: Modelling Approach and Uncertaintiesmentioning
confidence: 99%
“…Collier et al (2014) suggested that if the atmospheric surface layer is well mixed, then the water vapor partial pressure between the surface and the air may be assumed to be constant, thereby resulting in a latent heat flux based on the vapor pressure gradient. Fyffe et al (2014) also commented that the lower portion of the debris near the ice interface was observed to be saturated indicating that there may be evaporation and condensation occurring within the debris, albeit small, even when the surface relative humidity is less than 100 %. The lack of knowledge of the moisture in the debris and at its surface makes it difficult to accurately model the latent heat flux term.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, knowledge related to the latent heat flux on debris-covered glaciers is very limited. This has led previous studies to assume the surface is dry (Foster et al, 2012;Lejeune et al, 2013;Rounce and McKinney, 2014), assume it is dry unless the surface relative humidity was 100 % (Reid and Brock, 2010;Reid et al, 2012;Fyffe et al, 2014), assume a relationship between debris thickness and wetness (Fujita and Sakai, 2014), or use a reservoir approach to model the moisture in the debris (Collier et al, 2014). Collier et al (2014) suggested that if the atmospheric surface layer is well mixed, then the water vapor partial pressure between the surface and the air may be assumed to be constant, thereby resulting in a latent heat flux based on the vapor pressure gradient.…”
Section: Introductionmentioning
confidence: 99%
“…As such, accurate quantification of T a in distributed melt models is required for studies of glacier mass balance (e.g. Reijmer and Hock, 2008;Engelhardt andothers, 2013, Gabbi andothers, 2014), water resource availability (e.g. Nolin and others, 2010) and glacier contributions to sea-level rise (e.g.…”
Section: Introductionmentioning
confidence: 99%